Construction of a home-based rehabilitation nursing program integrating traditional Chinese and Western medicine for stroke patients based on mobile health - Xu, Yan; Yan, Zheng; Ye, Menghua; Huang, Xinrui; Huang, Luyi; Xu, Min (Frontiers in Neurology, 2025)
ObjectiveTo construct a home-based rehabilitation nursing program integrating traditional Chinese and Western medicine for stroke patients based on mobile health.MethodsThe initial framework of the program was established through evidence-based research. Subsequently, eight experts were invited to participate in an expert meeting to refine and finalize the program.ResultsFollowing systematic literature retrieval and screening, 30 relevant studies were selected for analysis. Through rigorous evidence extraction, synthesis, group discussion, and evaluation, a preliminary version of the program comprising 6 first-level items, 22 s-level items, and 51 third-level items was formulated. This draft was then reviewed by eight experts with an average authority coefficient of 0.9. After incorporating their feedback, the final program was revised to include 6 first-level items, 24 s-level items, and 51 third-level items.ConclusionThe home-based rehabilitation nursing program integrating traditional Chinese and Western medicine for stroke patients based on mobile health, demonstrates strong scientific validity and practical feasibility. It can serve as a valuable reference for clinical nursing practice.